SURGICAL TREATMENT OF POSTTRAUMATIC CHYLOUS ASCITES - B. Y. Sokolov; A. N. Smolyar; S. G. Gyulasaryan (Неотложная медицинская помощь)
We report a clinical case of successful surgical treatment of the victim with penetrating abdominal trauma of lumbar lymphatic cistern, complicated by chylous ascites.